Estudo de caso sobre falha em suporte de sensor de temperatura em gasoduto industrial - JESUS, Wellington Bruno Silva de (2021)
Currently, the number of failures that occur in welded industrial equipment is considerable. However, situations in which welded stainless steel structures have important flaws and / or loss of properties are uncommon, since this class of metals has good weldability and requires only special care in the process. The present work aims to characterize a stainless steel part, more specifically a flange used as a support in a pipeline to connect temperature sensors, which presents cracks that cause leakage in the pipe. The characterization was carried out by means of penetrating liquid tests; X-ray fluorescence; metallography; optical microscopy; scanning electron microscopy and Vickers microhardness. The results also made it possible to know the type of stainless steel, identification of cracks in the microstructure, as well as the chemical composition of the sample and the increase in hardness in regions close to the crack that can be associated with the welding process in the failure region. The results obtained in the tests performed, presented some phenomena in important stages of the device manufacturing process, such as the lack of penetration of the addition material in the base material and regions with different toughness, which may have contributed to the appearance of the crack.